Functional metabolomics revealed functional metabolic-characteristics of chronic hepatitis that is significantly differentiated from acute hepatitis in mice. (June 2022) - Wang, Tianyu; Hu, Longlong; Lu, Jiongjiong; Xiao, Mengqing; Liu, Jinging; Xia, Huiyu; Lu, Haitao
Abstract: Diagnosis and therapeutics of acute- and chronic- hepatitis (A-H and C-H) cannot be distinguished during clinical practice because functional molecular-characteristics of two conditions remains elusive. Here, we employed a functional metabolomics strategy to discover functional metabolites that can readily distinguish C-H from A-H in CCl4 treated mice. Metabolic-differentiation between A-H and C-H was identified as A-H was largely characterized by the dysregulated purine cycle and amino acid metabolism, while the disorders of hepatic taurine-conjugated bile acids and glycerolipid biosynthesis were observed with C-H. Excitingly, we found that the enhanced conversation of C18–22 PUFA-containing TAGs to MUFA-containing TAGs promoted the development of C-H, which was also closely associated with the changes of TCA intermediates regulated by gut microbiota (Muribaculaceae and Prevotellaceae) . Such metabolic discovery on hepatitis was validated by the functional annotation of metabolic genes, as the decreased expressions of Slc27a2, Acaa1a and Acaa1b mostly account for the dysregulation of purine degradation with AH, then the lowered expressions of Cyp2e1, Cat, Slc27a5 and Klb are significantly related to the dysregulated bile acids with C-H. Collecting clinical samples from the patients with hepatitis to compare serum metabolomes with A-H and C-H mice, the determinant functional metabolites were identified to significantly distinguish C-H from A-H in both experimental and clinical settings, suggesting metabolic discovery with CCl4 treated mice could be further efficiently explored to guide clinical research of A-H and C-H. Collectively, our study is providing novel insight into distinctive metabolic-characteristics of A-H and C-H underlying the innovative diagnosis and therapeutics of hepatitis. Graphical Abstract: ga1